Abdominal infectious complications associated with the dislocation of intraperitoneal part of drainage tube and poor drainage after major surgeries. Issue 5 (20th May 2020) - Guo, Yifan; Guo, Xu; Wang, Jia; Li, Kai; Xu, Guangzhong; Yan, Wei; Zhang, Jianlu; Lian, Dongbo; Fan, Qing; Han, Ziliang; Liu, Siqi; Wang, Wenping; et al.
Abstract: Abdominal drainage, serving as a diagnostic and therapeutic tool, has been widely applied to prevent complications after major abdominal surgical procedures. However, dislocation of intraperitoneal portion of drainage tube and poor drainage after major surgery has never been detailed. In this retrospective study, we determined whether postoperative abdominal infectious complications are attributed to dislocation of intraperitoneal portion of drainage tube. Patients were recruited from the Department of General Surgery at Beijing Shijitan Hospital, Capital Medical University, between June 2015 and June 2018. All of the enrolled patients had undergone different major abdominal surgical procedures with abdominal drainage. According to different fixation methods of the drainage tube, the patients were categorised as follows: group 1 as conventional extra‐abdominal fixation where the tubes were fixed on abdominal wall; group 2 as double fixation where the tubes were fixed by both extra‐abdominal and intra‐abdominal fixation. Among 60 patients (40 in group 1 and 20 in group 2) with suspected postoperative abdominal infection, abdominal computed tomography (CT) was performed to determine the presence of abnormality. Dislocation of drainage tubes, morbidity, treatment, and prognosis were compared between the two groups. None of the patients showed slip knot or drainage tube slipping from the abdomen based on physical examination and CT imaging. Drainage tube was fixed firmly on the abdominal wall. In group 1, 18 (45%) patients developed postoperative complications resulting from abdominal infection where severe dislocation of intraperitoneal portion of drainage tubes was confirmed by CT. Drainage tubes of six cases were significantly dislocated to the anterior abdominal wall from the target area; 7 upper abdominal drainage tubes dislocated to the lower abdomen; and 5 lower abdominal drainage tubes dislocated to the upper abdomen. Common complications included localised peritonitis (n = 4), abdominal abscess (n = 8), and anastomotic leakage (n = 6). Among them, 8 patients were cured by abdominal puncture catheter drainage; 5 underwent secondary operation and 5 were cured by conservative treatment. In group 2, no tube dislocation was identified by CT. Five patients (25%) developed complications, including localised peritonitis (n = 1), abdominal abscess (n = 1), and anastomotic leakage (n = 3). All the five patients were cured by conservative treatment. Postoperative abdominal infection complications can stem from dislocation of intraperitoneal portion of drainage tube and poor drainage after major abdominal surgery. Maintaining the intraperitoneal portion of drainage tube at the proper location, for example, by applying intraabdominal fixation, is paramount to decrease the incidence and severity of postoperative complications.